Representation of 21st Century Literacy (4C) in the Folklore Ular N'Daung by Dian Kristiani - Nofia Angela; Yulian Dinihari; Arifin; Dewi Sari Sumitro (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe the representation of 21st-century literacy, which encompasses four main competencies: critical thinking, creativity, collaboration, and communication (4Cs) in the folktale "Ular N'Daung" by Dian Kristiani. Folkklores, as a form of cultural literacy, serve not only as entertainment but also as educational media that instill moral values and character in the younger generation. In the context of 21st-century education, literary works should be studied through a literacy perspective to foster the development of critical thinking, creativity, collaboration, and effective communication skills. This study uses a qualitative descriptive method with a content analysis approach. The data source, the text of the Ular N'Daung story, is analyzed through intensive reading and systematic recording of narratives, quotations, and dialogues that represent aspects of 21st-century literacy. Data analysis follows the Miles and Huberman model, which includes data reduction, data presentation, and concludes with theoretical triangulation validation. The results of the study show that critical thinking is reflected in the ability of characters and readers to interpret the theme of struggle and moral messages, creativity is seen through the potential for adapting the story into digital media, collaboration is realized through the actions of the Youngest Princess who are full of empathy and responsibility, and communication is depicted in the dialogue between characters that convey human values. Thus, Ular N'Daung is not only a cultural heritage but also an effective literacy tool to develop character, empathy, and 4C skills in students in the digital era.